Lattice Boltzmann Modeling of Thermal Conduction in Composites with Thermal Contact Resistance (Communications in Computational Physics, 2018)
The effective thermal conductivity of composite materials with thermal contactresistance at interfaces is studied by lattice Boltzmann modeling in this work. Wemodified the non-dimensional partial bounce-back scheme, proposed by Han et al.[Int. J. Thermal Sci., 2008. 47: 1276-1283], to introduce a real thermal contact resistanceat interfaces into the thermal lattice Boltzmann framework by re-deriving the redistributionfunction of heat at the phase interfaces for a corrected dimensional formulation.The modified scheme was validated in several cases with good agreement between thesimulation results and the corresponding theoretical solutions. Furthermore, we predictedthe effective thermal conductivities of composite materials using this methodwhere the contact thermal resistance was not negligible, and revealed the effects ofparticle volume fraction, thermal contact resistance and particle size. The results inthis study may provide a useful support for materials design and structure optimization.